Children's and young adult literature a wonderful possibility in the education of children - Cespedes Almeida, Leidy Jazmin; Hurtado Almeida, Sandra Milena; Ortiz Gómez, Gloria Inés; Ulloa Jimenez, Cristina Liliana (Rastros Rostros, 2023)
The formation of readers and writers starts from the beginning of the conception of life and is a valuable possibility to lead the child to find a wonderful world if it is nurtured with play, language, imagination, joy and takes place in an environment that enhances curiosity, sensitivity, initiative and allows the practice of freedom, all in an attempt to dimension the child as a person.
Keywords: literature; education